Urine as a Specimen to Diagnose Infections in Twenty-First Century: Focus on Analytical Accuracy - Tuuminen, Tamara (Frontiers in Immunology, 2012)
Urine as a clinical specimen to diagnose infections has been used since ancient times. Many rapid technologies to assist diagnosis of infections are currently in use. Alongside traditional enzyme immunoassays (EIA), new technologies have emerged. Molecular analysis of transrenal DNA to diagnose infections is also a rapidly growing field. The majority of EIAs utilize the detection of excreted sugar compounds of the outer microbial cell wall shed into the bloodstream and excreted into the urine. This mini-review focuses on current knowledge on rapid urinary antigen detection tests to diagnose most common infections, and highlights their diagnostic utility. The past and the future of urinalysis are also briefly discussed. The analysis of the literature shows that some methods are not quantitative, and analytical sensitivity may remain suboptimal. In addition, the performance criteria and technical documentation of some commercial tests are insufficient. Clinical microbiologists and physicians should be alert to assay limitations.